2020
DOI: 10.3390/nu12123883
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patterns of Disturbed Eating in Psychosis: A Scoping Review

Abstract: Disturbed eating behaviours have been widely reported in psychotic disorders since the early 19th century. There is also evidence that antipsychotic (AP) treatment may induce binge eating or other related compulsive eating behaviours. It is therefore possible that abnormal eating patterns may contribute to the significant weight gain and other metabolic disturbances observed in patients with psychosis. In this scoping review, we aimed to explore the underlying psychopathological and neurobiological mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 117 publications
0
21
0
1
Order By: Relevance
“…Abnormalities in glucose regulation, lipid metabolism, feeding and energy sensing, have been reported from the earliest stages of illness, including the prodrome, and in unaffected siblings 4,43 . Furthermore, behavioral factors such as smoking, poor dietary habits, and low‐physical activity 59–65 ; biological factors such as increased inflammation, disruptions in the hypothalamic‐pituitary‐adrenal (HPA) axis, aberrant adipose tissue homeostasis, and brain insulin resistance 66–70 ; and systemic factors such as low socioeconomic status and barriers to care 71–73 interact and overlap to drive metabolic dysfunction, including the adiposity changes reported in the present study 8 …”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in glucose regulation, lipid metabolism, feeding and energy sensing, have been reported from the earliest stages of illness, including the prodrome, and in unaffected siblings 4,43 . Furthermore, behavioral factors such as smoking, poor dietary habits, and low‐physical activity 59–65 ; biological factors such as increased inflammation, disruptions in the hypothalamic‐pituitary‐adrenal (HPA) axis, aberrant adipose tissue homeostasis, and brain insulin resistance 66–70 ; and systemic factors such as low socioeconomic status and barriers to care 71–73 interact and overlap to drive metabolic dysfunction, including the adiposity changes reported in the present study 8 …”
Section: Discussionmentioning
confidence: 99%
“…Abnormal feeding behaviors observed in schizophrenic patients, including refusal to eat and, less commonly, pica, are often correlated to positive symptoms and dimensions of their psychopathology [ 4 , 5 ]. Pica may also be a manifestation of repetitive behaviors seen in schizophrenia [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that binge eating disorders and night eating syndromes are frequently found in people with schizophrenia and recommended regular screening for eating disorders in schizophrenia patients, but that review is now dated. Finally, and more recently, Stogios et al [32] performed a scoping review of disturbed eating in psychosis. While this is current, the study had a broad scope of including all psychotic disorders (including bipolar disorders) and all eating behaviors (including food preferences and dietary compositions) without assessing the strengths or weaknesses of individual studies, or providing a qualitative analysis of the reviewed studies.…”
Section: Introductionmentioning
confidence: 99%